In-situ carbide-reinforced CoCrFeMnNi high-entropy alloy matrix nanocomposites manufactured by selective laser melting: Carbon content effects on microstructure, mechanical properties, and deformation mechanism. (1st April 2021) - Kim, Young-Kyun; Yu, Ji-Hun; Kim, Hyoung Seop; Lee, Kee-Ahn
Abstract: The fabrication of high-entropy alloy (HEA) matrix nanocomposites by additive manufacturing (AM) is challenging due to that the control of defect-low sample having even distribution of reinforcement via AM is extremely hard. In this study, we investigated the effect of carbon content on the microstructure evolution, tensile properties, and deformation mechanisms of C x (Co20 Cr20 Fe20 Mn20 Ni20 )100– x ( x = 0.5, 1.0, and 1.5 at.%) HEA matrix nanocomposites additively manufactured by selective laser melting (hereafter referred to as SLM-built C-HEAs). SLM-built C-HEAs showed epitaxial growth grains, dislocation networks, and nano-sized carbides. In addition, with an increase in carbon content, the number density of nano-sized carbides, and the average grain sizes and columnar widths increased. In addition, the strength, work hardening rate, and elongation of SLM-built C-HEAs were enhanced as the carbon content increased. Dislocation networks in the as-built samples hindered the dislocation motion in the early to later stages of deformation, thus leading to high back stresses in SLM-built C-HEAs. Deformation twins were also formed in the three samples, because the critical stress for twinning was similar to the flow stresses at an early stage of deformation of SLM-built C-HEAs. Further, the yield strengths of SLM-built C-HEAs were predicted using six strengthening mechanisms that considered the microstructural factors. Based on the above findings, we discussed the correlations between the microstructure, mechanical properties, and deformation mechanisms of SLM-built C-HEAs with different carbon contents.